Reactions of a Silylyne Complex with Aldehydes: Formation of W−Si−O−C Four‐Membered Metallacycles and Their Metathesis‐Like Fragmentation. Issue 15 (19th February 2019) - Yoshimoto, Takashi; Hashimoto, Hisako; Takagi, Nozomi; Sakaki, Shigeyoshi; Hayakawa, Naoki; Matsuo, Tsukasa; Tobita, Hiromi
Abstract: A tungsten silylyne complex having a W≡Si triple bond reacted with two molecules of aldehydes at room temperature to give W−Si−O−C four‐membered metallacycles by [2+2] cycloaddition and subsequent formyl hydrogen transfer from one aldehyde molecule to another. Upon heating to 70 °C, the four‐membered metallacycles underwent metathesis‐like fragmentation cleanly to afford carbyne complexes and "silanoic esters, " in a manner similar to that of metallacyclobutadiene, an intermediate of alkyne metathesis reactions, and dimerization of the latter products gave 1, 3‐cyclodisiloxanes. The "silanoic ester" was also trapped by pivalaldehyde to give a [2+2] cycloaddition product in high yield. Abstract : A tungsten silylyne complex containing a W≡Si triple bond reacted with two molecules of aldehydes to give W−Si−O−C four‐membered metallacycles by [2+2] cycloaddition and subsequent formyl hydrogen transfer from one aldehyde molecule to another. The W−Si−O−C metallacycles underwent metathesis‐like fragmentation to afford carbyne complexes and "silanoic esters, " and dimerization of the latter products gave 1, 3‐cyclodisiloxanes (see scheme).